Using a Game to Educate About Sustainable Development - Gita Senka; Michela Tramonti; Alden Meirzhanovich Dochshanov; Triinu Jesmin; Jaanus Terasmaa; Hariklia Tsalapatas; Olivier Heidmann; Manuel Caeiro-Rodriguez; Carlos Vaz de Carvalho (Multimodal Technologies and Interaction)
Sustainable natural resource management is a high priority in the 21st century as it plays a crucial role in mitigating climate change and preventing some of its consequences like loss of biodiversity, land degradation, desertification, and the exhaustion of natural resources. This concern is reflected in the United Nations Sustainable Development Goals (SDGs), which emphasize, among other factors, sustainable cities and communities, responsible production and consumption, and climate action. Achieving sustainable natural resource management begins with raising awareness and educating the next generation. Therefore, it is essential to develop educational initiatives that prepare young people to become responsible and proactive adults in promoting environmental sustainability across industries and communities. Additionally, these initiatives should develop critical and analytical thinking skills, nurture innovative mindsets for creating environmentally sound solutions, and enhance the ability to collaborate within multidisciplinary teams. The NATURE project addressed these needs by designing and developing a serious educational game that fosters this set of skills. The results of the pilot testing show that the game is an effective tool and contributes to the education and awareness of the younger generation.